PEDAGOGICAL PROBLEMATICA IN THE ELUCIDATIVE PRESS OF LVOV H 20-30 ХХ ITEM - Silevich, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the attention is accented on the Ukrainian professional press 20-30th as to the source of study from history of pedagogic, histories of journalism, person researches. It is led to, that filling of these editions contains rich material not only for research of becoming and development of domestic science about education and study but also for finding out of development of national schooling in Galichini, which functioned in the difficult terms of the colonial mode.